2000
DOI: 10.2754/avb200069040327
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical and Haematological Values in Venous Blood of Farmed Red Deer (Cervus elaphus) at High Altitude

Abstract: Red deer, venous blood, biochemical values, haematology, high altitudeIn recent years red deer has been farmed in Mexico. Some biochemical and haematological analytes have been described in this species, however, their values depend mainly on nutrition, management and environmental conditions. Biochemical and haematological values are important for monitoring of health status and diagnosis of diseases. Great differences were described in values of plasma analytes, especially in concentrations of Na + and K + i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 18 publications
1
15
0
1
Order By: Relevance
“…The TP concentrations of both groups fall into the reference range of red deer (54-81 g/l), as reported by Kent et al (1980). Rosef et al (2010) reported on a lower TP interval (63.6-66.3 g/l) for free living deer in Norway, while high altitude (2 450 m) keeping (Mexico) led to higher values (50-80 g/l, Padilla et al 2000). Based on the above-mentioned results it was stated that elevated dietary protein content can significantly increase serum protein concentration of farmed red deer hinds.…”
Section: Blood Serummentioning
confidence: 87%
See 1 more Smart Citation
“…The TP concentrations of both groups fall into the reference range of red deer (54-81 g/l), as reported by Kent et al (1980). Rosef et al (2010) reported on a lower TP interval (63.6-66.3 g/l) for free living deer in Norway, while high altitude (2 450 m) keeping (Mexico) led to higher values (50-80 g/l, Padilla et al 2000). Based on the above-mentioned results it was stated that elevated dietary protein content can significantly increase serum protein concentration of farmed red deer hinds.…”
Section: Blood Serummentioning
confidence: 87%
“…To estimate the nutritional status and growth performance of Cervidae, blood sampling is the most widely used method (Reindeer and Svalbard Reindeer: Säkkinen et al 2001, reindeer: Ropstad et al 1997, Soppela et al 2008, Iberian red deer (Cervus elaphus hispanicus): Gaspar-López et al 2009, Rocky Mountain elk (Cervus elaphus nelsoni): Wolfe et al 1982, red deer: Rosef et al 2010, Soetrisno et al 1994, Kent et al 1980, Padilla et al 2000. Säkkinen et al (2001) proposed serum urea and creatinine and their quotient to estimate protein and energy intake.…”
Section: Introductionmentioning
confidence: 99%
“…The copper levels, however, are lowest among females and highest among stags, possibly because females excrete copper in the milk. Padilla et al (2000), however, found low serum Cu (9.86 µmol/L) values in young red deer kept on pasture. Values less than 8 µmol/L are below the critical level for Cu deficiency (Mackintosh et al, 1987).…”
Section: Discussionmentioning
confidence: 99%
“…Serum alkaline phosphatase concentration was above the expected normal range (41 to 116 U L (1 ; MAFRI, Veterinary Services Branch, Winnipeg, MB) and was higher (P 00.001) in steers grazing Control pastures relative to those on manured pastures. The implications of such high levels of alkaline phosphatase in steers on Control pastures are not immediately clear; however, alkaline phosphatase is generally used as an indicator of bone disease and liver failure (Padilla et al 2000). Serum alkaline phosphatase concentration was negatively correlated with serum urea N (r0(0.52; P 00.001).…”
Section: Blood Profilementioning
confidence: 99%
“…Concentration of serum gamma-glutamyl transferase, an indicator of liver damage (Quintavalla et al 2001), was higher (P 00.006) in steers on Split pastures, with no difference between steers on Control and Single pastures. Aspartate amino transferase is primarily used to diagnose and monitor the course of liver disease (Padilla et al 2000). Serum aspartate amino transferase concentration was highest (P 00.028) in steers on Split pastures, lowest on Control pastures, with intermediate values in steers on Single pastures (Table 4).…”
Section: Blood Profilementioning
confidence: 99%